Designing and Manufacturing of Grain Dryer Machine using Coconut Shell Fuel as an Alternative Heat Energy - Dermawan, Dermawan; Nur, Rusdi; Susanto, Tri Agus; Amrullah, Amrullah (Politeknik Negeri Ujung Pandang, 2021)
Many problems in the process of drying grain with a solar heat source. One of the factors is the erratic weather, where the rainy season comes along with harvest time. To overcome these obstacles, a grain dryer was designed that uses a rotary system that is simpler and more efficient and uses coconut shells as an alternative fuel. This study aims to obtain fast and affordable grain drying results by farmers using a rotary system dryer with coconut shell fuel. The benefit of this research is to provide an alternative solution for the community in dealing with harvesting in the rainy season by reducing land for drying grain. Equipment preparation was carried out in particular by using standard equipment to cut and connect the seat frame including the use of silencers and gasoline-fueled motors as propulsion and other supporting equipment. The components of each unit of grain drying machine are assembled and tested in stages according to procedures and functions. The test results show that the use of coconut shell can reach drying temperatures faster than the use of LPG, coconut shell fuel is better at reducing the moisture content of grain than the use of LPG. Testing of coconut shell fuel is done by drying 30 kg of grain for 20 minutes and 15 minutes. It can be concluded that the use of coconut shell as an alternative fuel can achieve a faster drying temperature than the use of LPG fuel. The use of coconut shell fuel to dry 30 kg of grain and reach a moisture content of up to 12% requires an effective time of 15 minutes.